The Role of Digital Marketing Interventions in E-Advocacy Leverage Capacity: A Culinary Business Breakthrough to Counter the COVID-19 Pandemic - Ahmad Ikhwan Setiawan; Annisa Pratiwi Hendraningsih; Sri Rahayu; Amina Sukma Dewi (Faculty of Economics and Business, Universitas Gadjah Mada, 2022)
Introduction/Main Objectives: This research aims to study the important factors behind achieving the e-advocacy leverage capacity that determines the success of a business in the sphere of digital marketing. Background Problems: In response to the increasing competition in the world of online culinary businesses due to the COVID-19 pandemic, businesses have to enhance strategic marketing to improve consumer loyalty. Novelty: This research model contributes to the development of a concept about consumer advocacy from the perspective of strategic marketing, which is still a limited area of study. Research Methods: The research model was applied to 220 respondents (Indonesian culinary business owners) using a survey that was processed with AMOS SEM. Finding/Results: This research convincingly identifies two significant building factors for e-advocacy leveraged capacity, namely promotional attractiveness and digital affinity direction. Conclusion: Companies’ marketing strategies focus not only on maintaining close customer relations but also on ways to intervene with customers so that they are willing to advocate products or brands through digital media.